PROBLEMS AND PARADOXES OF INFORMATION SECURITY IN MODERN MANAGEMENT - Elena P. Guseva (Статистика и экономика, 2016)
The aim of this article is to study theproblems and paradoxes of informationsecurity (IS) in a modern, ﬁrst of all, the Russian management, and preservationof information and its protection fromthreats, guarantee of completeness andaccuracy of the output data, minimize itslosses and distortion. The recommendation of application of SMART managementin services of providing IB.